(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Sexual dimorphism is required in cases of natural disasters, recognition of fragmented bones and beyond forensic iden tification. Pyriform aperture (PA) is a pear-shaped structure in the human skull, bounded by the frontal process of maxillary bone on the lateral aspect, and the nasal bones in upper. Data from the present study shows that various measurements taken from pyriform aperture and nasal bones can be a useful forensic tool in sexual dimorphism.